Build it and they will come: integrating unique collections and undergraduate research. Issue 4 (5th October 2015) - Cook, Matthew
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The "build it and they will come approach" is a largely accepted proposition in the library community, particularly in the area of special collections. There is, at times, little critical analysis given to collection development, digitization efforts or information literacy instruction in regard to how these hard-to-serve but research-rich materials might be used in the classroom. Instead, there exists a benevolent know-it-all expert determining which collections warrant preservation, digitization, acquisition and, ultimately, attention. At California State University (CSU) Channel Islands (CI), the user – teachers and students – is the focus of all special collection activities, and we have devised innovative ways to both encourage students and faculty to engage these materials as well as foster their appreciation, awareness and use on campus. Design/methodology/approach – This paper explores three ways that librarians at the John Spoor Broome Library encourage and facilitate the use of primary documents housed in unique collections to support undergraduate student research. Findings – The use of high-impact teaching practices, like undergraduate research, is an important tool in promoting retention and increasing graduation rates, particularly for underrepresented minorities. At CSU CI and the John Spoor Broome Library, engaging students with primary documents is a focus of unique collections work that benefits both students and the Library alike. Originality/value – Digitization is a key component of most special collections work in the library world today, but perhaps efforts focused on promoting use are lacking. At CI, use is the primary focus of all unique collections work and, thus, could be a model for other libraries and archive departments.